2014
DOI: 10.1017/s1479262114000021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity inVicia fabaL. populations cultivated in Tunisia revealed by simple sequence repeat analysis

Abstract: Faba bean (Vicia faba L.) is one of the most important legumes in the world. Little is known about the genetic resources of faba bean in Southern Tunisia. In the present study, genetic diversity within Tunisian faba bean germplasms was investigated using 16 simple sequence repeat markers. In total, 50 alleles were detected. The number of alleles per marker ranged from 2 to 6, with an average of 3. Genetic diversity and polymorphism information content values averaged, respectively, 0.43 (range 0.34–0.51) and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…In addition, the ICARDA derived lines named with Flip10 and Flip03 prefixes were explicitly separated in this respect. The mean Nei's (1973) gene diversity (0.40) in the faba bean genotypes was similar to that obtained by Yahia et al [30], who reported a mean value of 0.43, using 16 Tunisian faba bean local populations and 16 polymorphic SSR markers. In the present study, mean effective number of alleles (1.67) was lower than that (2.25) obtained by Yahia et al [30] and relatively similar to Wang et al [31], who studied genetic diversity and relatedness of 802 faba bean genotypes using 11 intersimple sequence repeat (ISSR) primers and found a mean value of 1.3888.…”
Section: Resultssupporting
confidence: 85%
“…In addition, the ICARDA derived lines named with Flip10 and Flip03 prefixes were explicitly separated in this respect. The mean Nei's (1973) gene diversity (0.40) in the faba bean genotypes was similar to that obtained by Yahia et al [30], who reported a mean value of 0.43, using 16 Tunisian faba bean local populations and 16 polymorphic SSR markers. In the present study, mean effective number of alleles (1.67) was lower than that (2.25) obtained by Yahia et al [30] and relatively similar to Wang et al [31], who studied genetic diversity and relatedness of 802 faba bean genotypes using 11 intersimple sequence repeat (ISSR) primers and found a mean value of 1.3888.…”
Section: Resultssupporting
confidence: 85%
“…These remarks were also observed for TL6 (local) and TL15 (Romania). This result concurs with those found by Lazrek et al (2009) and Yahia et al (2014), who used molecular markers with plant species (Medicago truncatula and Vicia faba L., respectively) and showed the presence of divergence between genetic clusters and geographical origins for the different cultivars studied. The group C included two introduced accessions (TL12 and TL14).…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with our SSR results. Also in Tunisia, Yahia, Hannachi [ 53 ] found a correlation between SSR alleles and seed size, fitting the “ major , minor , equina” classification. Likewise, Terzopoulos and Bebeli (8)] could see a separation of minor types from other faba bean types in a PCA plot based on the allele frequency data for four ISSR markers.…”
Section: Resultsmentioning
confidence: 90%